Zygon's 1996 Expedition into Neuroscience and Religion - Albright, Carol Rausch (Zygon, 1996)
Abstract. Neuroscience is in a period of explosive growth. To address the implications of the new findings for religion and science, Zyvon in 1996 published fifteen articles in this field. Although the authors'explorations of neuroscience and religion are various, three issues in particular are addressed repeatedly: (1) the nature of human identity, or hallmarks of humanness; (2) the nature and origin of religious consciousness; and (3) our means of discovering or constructing order and integration in the brain/mind, in the environment, and holistically. With these categories as templates, this article correlates the findings of the Zygon neuroscience contributors of 1996.